Parental Perspectives on Teachers' Supportive Strategies During the Transition to First Grade - Dor, Asnat (Advances in Social Sciences Research Journal, 2024)
This qualitative study explores the transition to first grade, focusing on parental expectations and the perceived supportiveness of educational staff. The objectives are to identify the primary expectations and needs of parents from teachers, and to evaluate the extent and methods through which parents view educational staff as a source of support and information. Twenty parents participated in semi-structured interviews, revealing their concerns and expectations as their children entered first grade. Thematic analysis identified key themes: the necessity for accessible communication, genuine teacher attentiveness, and comprehensive information transparency. Findings suggest that strengthening communication, teacher responsiveness, and proactive information sharing are crucial to supporting both parents and children. These insights highlight how enhanced teacher training and school policies can better address parental needs, promoting a smoother transition into first grade and improving early educational experiences.